Providone?iodine in experimental peritoneal hydatidosis - Kolbakir, F.; Erk, M.K.; Gökçe, Ö. (My University, 1992)
[Abstract Not Available]
Keywords: Animal; Echinococcosis; Peritoneal Diseases; Povidone-Iodine; Rats; povidone iodine; animal experiment; bacterial infection; controlled study; echinococcosis; letter; nonhuman; priority journal; rat